2008
DOI: 10.1093/hmg/ddn055
|View full text |Cite
|
Sign up to set email alerts
|

Superovulation alters the expression of imprinted genes in the midgestation mouse placenta

Abstract: Imprinted genes play important roles in embryonic growth and development as well as in placental function. Many imprinted genes acquire their epigenetic marks during oocyte growth, and this period may be susceptible to epigenetic disruption following hormonal stimulation. Superovulation has been shown to affect growth and development of the embryo, but an effect on imprinted genes has not been shown in postimplantation embryos. In the present study, we examined the effect of superovulation/in vivo development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
138
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(148 citation statements)
references
References 70 publications
7
138
1
2
Order By: Relevance
“…Moreover, most of the imprinted genes studied, independent of their imprinting status (maternal or paternal), suffered delayed upregulation in conceptuses transferred to an asynchronous environment, which may simply reflect developmental retardation. On the other hand, imprinted genes are known to be susceptible to epigenetic modification in response to environmental perturbations during early pregnancy [18,21,22]. To examine whether there was any rationale to suspect epigenetic alteration, we also examined expression of DNA methyltransferase genes, which regulate gene function by maintaining genome methylation (DNMT1) or establishing de novo methylations (DNMT3a and DNMT3b) [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, most of the imprinted genes studied, independent of their imprinting status (maternal or paternal), suffered delayed upregulation in conceptuses transferred to an asynchronous environment, which may simply reflect developmental retardation. On the other hand, imprinted genes are known to be susceptible to epigenetic modification in response to environmental perturbations during early pregnancy [18,21,22]. To examine whether there was any rationale to suspect epigenetic alteration, we also examined expression of DNA methyltransferase genes, which regulate gene function by maintaining genome methylation (DNMT1) or establishing de novo methylations (DNMT3a and DNMT3b) [40].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, paternally expressed genes generally enhance fetal growth, whereas maternally expressed genes restrict it [20]. Moreover, recent studies have shown that environmental factors can affect early embryo development and expression of developmentally important and/or placentally imprinted genes, presumably by epigenetic dysregulation [18,21,22]. Imprinted genes may, therefore, be particularly sensitive to epigenetic alterations as a result of an inappropriate or altered environment during early embryo development [21].…”
Section: Introductionmentioning
confidence: 99%
“…No Imprinted in E10 placenta and E13 yolk sac Ono et al (2003), Wang et al (2011) and Okae et al (2012) Conflicting data from E13.5 placenta following embryo transfer to eliminate decidual contamination Biallelic in E17.5 placenta and neonate Biallelic in TS cells Lee et al (2000) and Okae et al (2012) Imprinted in embryo and brain No Imprinted in E13.5 and E17.5 placenta, embryo and neonate Kim et al (1999), Wang et al (2011) and Okae et al (2012) Biallelic in neonatal and adult brain No Imprinted in all tissues examined from wE7.5 Leff et al (1992), Barr et al (1995), Gray et al (1999), de los Santos et al (2000 and Fortier et al (2008) Placental imprinting analysis complicated by maternal contamination Imprinted in TS cells …”
Section: Conflicting Datamentioning
confidence: 99%
“…Multiple studies of embryos fertilised and cultured in vitro have suggested that imprinting control elements may be more susceptible to the environment during this period than previously thought [38,39]. However, these studies are potentially confounded by the effects of superovulation, which has been shown to alter the epigenetic status of maternal ICRs [40].…”
Section: The Role Of Imprinted Genes In Developmental Plasticity In Rmentioning
confidence: 99%